TERRITORIAL LOSSES OF GEORGIA IN THE WAR WITH RUSSIA IN 2008 AND THEIR INFLUENCE ON THE FUTURE OF THE GEORGIA- RUSSIA CONFLICT - Целуйко, В.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Territorial losses of Georgia in the war in august 2008 is considered in the article. The role of each of this territories for Georgia, Russia, Abkhazia and South Ossetia is analysed. Positive and negative political factors from reconfiguration of positions for sides of the conflict is analysed too. The influence of territorial losses of Georgia in the war on the progress of the Georgia-Russia conflict is forecasted.